A topographical and surgical anatomical description of the recurrent laryngeal nerve in adult and paediatric populations of South Africa - Kiluba, Joshua Boanerges Lusamba (My University, 2019)
The prevalence of post-surgical injury of the recurrent laryngeal nerve (RLN) globally is at most 11%. There is currently an overwhelming amount of literature on the anatomy of the RLN and the advent of intraoperative neural monitoring. Most of the available literature describes the normal anatomy of the RLN in adult cadavers, less in adult patients with neck masses and least in paediatric patients. Thyroid surgery in paediatric patients has not been thoroughly researched despite the notable increase in thyroid neoplasms in this population.
Dissertation submitted to the Faculty of Health Sciences of the University of the Witwatersrand, Johannesburg in fulfilment of the requirement for the degree of Master of Science in Medicine, Johannesburg, 28th October 2019
Keywords: Thyroid gland--Surgery; Thyroidectomy